If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(2y + -3) + -1y = -2(y + -5) Reorder the terms: -4(-3 + 2y) + -1y = -2(y + -5) (-3 * -4 + 2y * -4) + -1y = -2(y + -5) (12 + -8y) + -1y = -2(y + -5) Combine like terms: -8y + -1y = -9y 12 + -9y = -2(y + -5) Reorder the terms: 12 + -9y = -2(-5 + y) 12 + -9y = (-5 * -2 + y * -2) 12 + -9y = (10 + -2y) Solving 12 + -9y = 10 + -2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2y' to each side of the equation. 12 + -9y + 2y = 10 + -2y + 2y Combine like terms: -9y + 2y = -7y 12 + -7y = 10 + -2y + 2y Combine like terms: -2y + 2y = 0 12 + -7y = 10 + 0 12 + -7y = 10 Add '-12' to each side of the equation. 12 + -12 + -7y = 10 + -12 Combine like terms: 12 + -12 = 0 0 + -7y = 10 + -12 -7y = 10 + -12 Combine like terms: 10 + -12 = -2 -7y = -2 Divide each side by '-7'. y = 0.2857142857 Simplifying y = 0.2857142857
| 2+-5+-3= | | 41/45-1/27 | | 5x(6)-4= | | 3a-4a=4 | | -8=x/-7-10 | | -8=x/-7-10 | | X-6+x=10 | | -(-9)-5+(4)= | | -75+9x-x=69 | | 7/5*5/14 | | 42=7(x+4) | | 2.6(-2-8x)=-6-19.4x | | 0.50x+0.30(40)=0.25(134) | | x=(2y+5)-50 | | -2x^2+3x+4=13x-5x^2+1 | | 3+2z=5z-3-3z+6 | | 4c-19=17 | | -4c-9.6+5c=o | | -75+9x-x=9 | | 4-i(3b-8)=2b-17 | | 8x-3x+2=x-9+11 | | 2q^2+2q+24=0 | | 2b+3b=-10 | | 70+11x+11=180 | | (3x/4)-(1/3)=1-(2/3)-(1/6) | | 70+11x=180 | | 8x-x+2=x-9+11 | | 0x-4=6 | | 4y+5=4y+2 | | 20a-2a+32=12a-6 | | 5x+10/5=-4 | | 3=m/14+4 |